A method for preparing perovskite quantum dot SiO2 composite material

By using the combination of Lewis acid/base oxysilane with lead, cesium source and ligand, the preparation process of perovskite quantum dot SiO2 composite materials is simplified, solving the problems of cumbersome steps and unstable composite structure in the existing methods. , achieving efficient and stable quantum dot coating effect.

CN116179182BActive Publication Date: 2025-02-18WUXI UTMOST LIGHT TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211715143.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-02-18
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

The existing perovskite quantum dot SiO2 composite materials preparation methods are cumbersome, the process is long and the composite structure formed is unstable.

Method used

Lewis acid/alkalioxysilane is used as SiO2 precursor, mixed with lead, cesium source and ligand, heated and vacuumed, then reheated in a nitrogen environment, and the hydrogen halogen acid solution is injected into the reaction system. , forming a perovskite quantum dot SiO2 composite material.

Benefits of technology

The preparation process is simplified, the water and oxygen resistance of quantum dots is improved, and a PQDs@SiO2 composite structure with good stability is formed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116179182B_ABST
    Figure CN116179182B_ABST
Patent Text Reader

Abstract

The present invention provides a perovskite quantum dot SiO 2 A method for preparing a composite material, the method comprising: (1) mixing a lead source, a cesium source, a ligand, and a Lewis acid / Lewis base oxysilane with a solvent, and performing a first heating and vacuuming to obtain a first reaction system; (2) replacing the first reaction system in step (1) with a nitrogen environment, and performing a second heating to obtain a second reaction system; (3) injecting a hydrohalic acid solution into the second reaction system in step (2) for reaction, and cooling and separating after the reaction to obtain a perovskite quantum dot SiO 2 Composite material. Compared with the traditional quantum dot preparation method, the preparation method does not require an additional precursor preparation step, the halogen source is a hydrohalic acid aqueous solution without any processing after purchase, the synthesis method is efficient and simple, and can greatly improve the water and oxygen resistance of quantum dots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of quantum dot material preparation, and relates to a method for preparing a perovskite quantum dot composite material, and in particular to a method for preparing a perovskite quantum dot SiO2 composite material. Background Art

[0002] With the rapid development of science and technology, traditional display technology can no longer meet people's demand for high-definition color display. Since Sony launched quantum dots in 2013, quantum display has spread across various display fields with the unique color performance of quantum dots. Quantum dot materials have once become a hot topic in the display field and among researchers. However, cadmium-based quantum dots, which have mature preparation processes and good stability, have been affected by the cadmium restriction order issued by the European Union and have stopped on the road to industrialization. It is worth mentioning that the outstanding performance of perovskite quantum dots with high quantum yield, adjustable emission, wide color gamut, and high purity and cadmium-free in the field of display applications can meet its application needs. However, the insufficient stability of perovskite quantum dots has become an urgent problem to be solved in their industrial applications. To this end, researchers have racked their brains to come up with various coping strategies. As early as 2016, a research group proposed to synthesize quantum dots by providing -NH2 as a ligand in the synthesis process of APTES, and then complete the hydrolysis of APTES to form SiO2 through open stirring and other processes, but this process is relatively long, ranging from three or four hours to more than ten hours. Since then, reports on SiO2-coated perovskite quantum dots have sprung up like mushrooms after rain. In 2018, the article <10.1088 / 1361-6528 / aac00b> proposed to coat perovskite quantum dots by adding TMOS post-treatment after synthesizing quantum dots. In 2019, <10.1016 / j.ceramint.2019.10.114> proposed that by synthesizing quantum dots at room temperature, APTES was added in the form of post-treatment to further form SiO2 products; in 2021, <10.1016 / j.jcrysgro.2021.126045> proposed that by introducing TEOS in the form of post-treatment based on room temperature recrystallization to form a PQDs@SiO2 complex; recently, <10.1021 / acsanm.2c02560> proposed that the precursor of perovskite quantum dots and mesoporous SiO2 were calcined together at a high temperature of 600°C to form a PQDs@SiO2 composite material.

[0003] The existing PQDs@SiO2 preparation methods have the following shortcomings. In terms of coating methods, most of the existing coating methods are to first synthesize perovskite quantum dots, and then coat them by stirring, calcining and other means in the form of post-processing. The steps are relatively cumbersome and the process takes several hours or even more than ten hours, which is relatively long. In terms of the mechanism of action, most of the traditional coating methods are ligand exchange between SiO2 precursors and ligands on the surface of perovskite quantum dots and then hydrolyze them. However, the SiO2 precursors that interact with PQDs in the form of ligand exchange are limited, and it is difficult to form a PQDs@SiO2 composite structure with good stability. Or it is directly hydrolyzed to form a complex with perovskite quantum dots, which has no interaction with quantum dots. The structure of the formed complex is loose and unstable. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing a perovskite quantum dot SiO2 composite material. Compared with the traditional quantum dot preparation method, the preparation method does not require an additional precursor preparation step, and the halogen source is a hydrohalic acid aqueous solution without any processing after purchase. The synthesis method is efficient and simple, and can greatly improve the water and oxygen resistance of the quantum dots.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a perovskite quantum dot SiO2 composite material, the preparation method comprising:

[0007] (1) mixing a lead source, a cesium source, a ligand, and a Lewis acid / Lewis base oxysilane with a solvent, and performing a first heating and vacuuming to obtain a first reaction system;

[0008] (2) replacing the first reaction system in step (1) with a nitrogen environment, and performing a second heating to obtain a second reaction system;

[0009] (3) Injecting the hydrohalic acid solution into the second reaction system of step (2) to react, and cooling and separating after the reaction to obtain the perovskite quantum dot SiO2 composite material.

[0010] In the present invention, the SiO2 precursor is selected as Lewis acid / base oxysilane, that is, the other end of the Lewis acid / base is connected to the oxysilane group, and is added together with the perovskite quantum dot precursor before synthesis. In the early stage, it acts as a Lewis acid / base ligand to synergistically prepare quantum dots, so that the Lewis acid / base oxysilane can be stably anchored on the ligand surface as a ligand before hydrolysis, and forms a PQDs@SiO2 composite material after hydrolysis in the later stage, thereby ensuring that the perovskite quantum dots are coated.

[0011] In the present invention, after the hydrohalic acid aqueous solution is injected, the nucleation and crystallization of the quantum dots are very fast, and at the same time, a large amount of water vapor environment is provided for the hydrolysis of Lewis acid / alkali silane. After the quantum dot reaction is completed, a PQDs@SiO2 composite material can be formed.

[0012] As a preferred technical solution of the present invention, the molar ratio of the cesium source to the lead source in step (1) is 10:1 to 1:10, such as 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] Preferably, the molar ratio of the ligand to the lead source is 5:1 to 2:1, such as 5:1, 4.5:1, 4:1, 3.5:1, 3:1, 2.5:1 or 2:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Preferably, the molar ratio of the Lewis acid / Lewis base oxysilane to the lead source is 25:1 to 5:1, such as 25:1, 22:1, 20:1, 18:1, 15:1, 12:1, 10:1, 8:1 or 5:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the molar ratio of the lead source to the solvent is 1:200 to 1:50, such as 200:1, 180:1, 150:1, 120:1, 100:1, 80:1 or 50:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] In the present invention, if the molar ratio of Lewis acid / alkali oxysilane to the lead source is greater than 25:1, the added amount is too much, the quantum dots have more ligands on the surface, and it is not easy to nucleate and crystallize and grow; if the molar ratio of Lewis acid / alkali oxysilane to the lead source is less than 5:1, the added amount is less, the quantum dots have more defects, and thus the QY is lower.

[0017] As a preferred technical solution of the present invention, the lead source in step (1) includes lead oxide and / or lead acetate.

[0018] Preferably, the cesium source includes any one of cesium carbonate, cesium acetate or cesium bicarbonate, or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of cesium carbonate and cesium acetate, a combination of cesium acetate and cesium bicarbonate, a combination of cesium bicarbonate and cesium carbonate, or a combination of cesium carbonate, cesium acetate and cesium bicarbonate, etc.

[0019] Preferably, the ligand comprises a Lewis acid ligand and / or a Lewis base ligand.

[0020] Preferably, the Lewis acid ligand comprises any one of oleic acid, dodecylbenzenesulfonic acid or trioctyl phosphine or a combination of at least two thereof. Typical but non-limiting examples of the combination include: a combination of oleic acid and dodecylbenzenesulfonic acid, a combination of dodecylbenzenesulfonic acid and trioctyl phosphine, a combination of trioctyl phosphine and oleic acid, or a combination of oleic acid, dodecylbenzenesulfonic acid and trioctyl phosphine, etc.

[0021] Preferably, the Lewis base ligand comprises any one of oleylamine, n-octylamine or thiol, or a combination of at least two thereof. Typical but non-limiting examples of the combination include: a combination of oleylamine and n-octylamine, a combination of n-octylamine and thiol, a combination of thiol and oleylamine, or a combination of oleylamine, n-octylamine and thiol, etc.

[0022] As a preferred technical solution of the present invention, the structure of the Lewis acid / Lewis base oxysilane in step (1) is shown in Formula 1:

[0023]

[0024] The wavy line segment is a straight-chain or branched alkyl group, and R includes any one of an amino group, a thiol group, a carboxyl group, a sulfonic acid group or a TOPO group, or a combination of at least two of them.

[0025] In the present invention, when R is an electron-donating group such as an amino group, it is a Lewis base oxysilane, and when R is an electron acceptor group such as a mercapto group or a carboxyl group, it is a Lewis acid oxysilane.

[0026] In the present invention, the straight chain or branched alkyl group includes methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, methylene, ethylene, propylene, butylene, pentylene or hexylene, etc. The above groups are only examples and are not limited to the above-mentioned groups.

[0027] Preferably, the Lewis acid / Lewis base oxysilane in step (1) comprises any one or a combination of at least two of 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-mercaptopropyl trimethoxysilane or 3-mercaptopropyl triethoxysilane, isocyanatopropyl triethoxysilane, and 3-isocyanatopropyl) triethoxysilane. Typical but non-limiting examples of the combination include: a combination of 3-aminopropyl triethoxysilane and 3-aminopropyl trimethoxysilane, a combination of 3-aminopropyl trimethoxysilane and 3-mercaptopropyl trimethoxysilane, a combination of 3-mercaptopropyl trimethoxysilane and 3-mercaptopropyl triethoxysilane, a combination of 3-mercaptopropyl triethoxysilane and 3-aminopropyl triethoxysilane, or a combination of 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane and 3-mercaptopropyl trimethoxysilane, etc.

[0028] As a preferred technical solution of the present invention, the solvent in step (1) includes any one of liquid paraffin, trioctyl phosphine or octadecene, or a combination of at least two thereof.

[0029] As a preferred technical solution of the present invention, the terminal temperature of the first heating in step (1) is 80-110°C, such as 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the vacuuming time in step (1) is 20 to 40 min, such as 20 min, 22 min, 25 min, 28 min, 30 min, 32 min, 35 min, 38 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] As a preferred technical solution of the present invention, the terminal temperature of the second heating in step (2) is 150-180°C, such as 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] As a preferred technical solution of the present invention, the hydrohalic acid solution in step (3) is a mixed solution obtained by diluting a hydrohalic acid aqueous solution in an organic solvent.

[0033] Preferably, the hydrohalic acid includes any one of hydrobromic acid, hydrochloric acid or hydroiodic acid, or a combination of at least two of them.

[0034] Preferably, the organic solvent comprises oleic acid.

[0035] Preferably, the molar ratio of the hydrohalic acid to the lead source is 10:1 to 3:1, such as 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1 or 3:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] As a preferred technical solution of the present invention, the reaction time of step (3) is 2 to 5 minutes, such as 2 minutes, 2.5 minutes, 3 minutes, 3.5 minutes, 4 minutes, 4.5 minutes or 5 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] As a preferred technical solution of the present invention, the cooling in step (3) includes natural cooling or cooling to room temperature in a water bath.

[0038] In the present invention, the separation treatment method includes: taking the cooled reaction solution, adding twice the amount of n-hexane, centrifuging and purifying twice, and drying to obtain a powdery product PQDs@SiO2, or the cooled reaction solution is allowed to stand for three days to form a gel-like product PQDs@SiO2.

[0039] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0040] (1) Compared with the traditional hot injection quantum dot synthesis method, no additional precursor preparation step is required, and the halogen source is a hydrohalic acid purchased without any processing, and the hydrohalic acid can be directly injected;

[0041] (2) There are many choices of SiO2 precursors in forming PQDs@SiO2 composite materials, not only the most commonly used materials such as APTES and 3-aminopropyltrimethoxysilane, but also Lewis base oxysilane with acidic groups. The selection range of precursors is very wide;

[0042] (3) The other end of the Lewis acid and base is connected to the oxysilane group, which is added together with the perovskite quantum dot precursor before synthesis. In the early stage, it acts as a Lewis acid and base ligand to coordinately prepare quantum dots, so that the Lewis acid / base oxysilane can be stably anchored on the ligand surface as a ligand before hydrolysis. In the later stage, the oxysilane is hydrolyzed to coat the perovskite quantum dots, thereby ensuring that the hydrolysis products formed by hydrolysis are stably present on the surface of the quantum dots;

[0043] (4) Since the injected halogen source is hydrohalic acid, the nucleation and crystallization of quantum dots are very fast. The hydrohalic acid with high water content provides a large amount of water vapor environment for the hydrolysis of Lewis acid / alkali silane during injection. After the quantum dot reaction is completed, the PQDs@SiO2 composite material can be quickly formed;

[0044] (5) A gel or powder product can be obtained by treating the reaction solution;

[0045] (6) The PQDs@SiO2 composite material prepared by the preparation method can greatly improve the water and oxygen resistance of quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 is a flow chart for preparing the perovskite quantum dot SiO2 composite material provided in Example 1;

[0047] Figure 2a It is a QY comparison spectrum of Example 1 and Comparative Example 1;

[0048] Figure 2b This is the QY spectrum of the PQDs@SiO2 gel prepared in Example 1;

[0049] Figure 2c This is the QY spectrum of the PQDs@SiO2 powder prepared in Example 1;

[0050] Figure 3a This is a real picture of the cooling process of the PQDs@SiO2 composite prepared in Example 1;

[0051] Figure 3b This is a physical picture of the PQDs@SiO2 gel prepared in Example 1;

[0052] Figure 3c This is a physical picture of the PQDs@SiO2 powder prepared in Example 1.

[0053] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0055] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:

[0056] Example 1

[0057] This embodiment provides a method for preparing a perovskite quantum dot SiO2 composite material, the process of which is as follows: Figure 1 As shown, the preparation method comprises:

[0058] (1) Weigh 1 ml of oleic acid, 0.64 ml of APTES, 0.0446 g of lead oxide, and 0.0325 g of cesium carbonate and dissolve them in 10 ml of L ODE. Slowly heat to 100 °C in vacuum and maintain for 30 min.

[0059] (2) The reaction system was switched to a N2 protective environment and slowly heated to 160°C;

[0060] (3) Take 0.128 ml of HBr diluted in ODE and quickly inject it into the reaction system. After three minutes of reaction, cool it down to room temperature in a water bath;

[0061] (4) After cooling, the reaction solution is added with twice the amount of n-hexane, centrifuged and purified twice, and then dried to obtain a powdery product PQDs@SiO2. Alternatively, the reaction solution is allowed to stand for three days to form a gel-like product PQDs@SiO2.

[0062] Example 2

[0063] In this embodiment, except that APTES is replaced by 3-aminopropyltrimethoxysilane, other conditions are the same as those in Embodiment 1.

[0064] Example 3

[0065] In this embodiment, except that APTES is replaced by 3-mercaptopropyltriethoxysilane, other conditions are the same as those in Embodiment 1.

[0066] Example 4

[0067] In this embodiment, except that APTES is replaced by 3-mercaptopropyltrimethoxysilane, other conditions are the same as those in Embodiment 1.

[0068] Example 5

[0069] In this example, except that the hydrobromic acid in step (3) is replaced by hydroiodic acid, the other conditions are the same as those in Example 1.

[0070] Example 6

[0071] In this example, except that the hydrobromic acid in step (3) is replaced by hydrochloric acid, the other conditions are the same as those in Example 1.

[0072] Example 7

[0073] This embodiment provides a method for preparing a perovskite quantum dot SiO2 composite material, the preparation method comprising:

[0074] (1) Weigh 1.32 ml (3-isocyanatopropyl) triethoxysilane, 1 ml oleylamine, 0.0446 g lead oxide, and 0.0325 g cesium carbonate and dissolve them in 10 ml L ODE, and slowly heat to 80°C to 110°C in vacuum and maintain for 20 to 40 minutes; (the molar ratio of Lewis acid oxysilane to lead source is 25:1);

[0075] (2) The reaction system is switched to a N2 protective environment and slowly heated to 150-180°C;

[0076] (3) Take 0.128 ml of HBr diluted in ODE and quickly inject it into the reaction system. After reacting for 2 min, cool it to room temperature in a water bath;

[0077] (4) After cooling, the reaction solution is added with twice the amount of n-hexane, centrifuged and purified twice, and then dried to obtain a powdery product PQDs@SiO2. Alternatively, the reaction solution is allowed to stand for three days to form a gel-like product PQDs@SiO2.

[0078] Example 8

[0079] This embodiment provides a method for preparing a perovskite quantum dot SiO2 composite material, the preparation method comprising:

[0080] (1) Weigh 0.125 ml of isocyanatepropyltriethoxysilane, 1 ml of oleylamine, 0.0446 g of lead oxide, and 0.0325 g of cesium carbonate and dissolve them in 10 ml of L ODE. Slowly heat to 80-110° C. in vacuum and maintain for 20-40 min; (the molar ratio of Lewis acidoxysilane to lead source is 5:1).

[0081] (2) The reaction system is switched to a N2 protective environment and slowly heated to 150-180°C;

[0082] (3) Take 0.128 ml of HBr diluted in ODE and quickly inject it into the reaction system. After reacting for 5 min, cool it to room temperature in a water bath;

[0083] (4) After cooling, the reaction solution is added with twice the amount of n-hexane, centrifuged and purified twice, and then dried to obtain a powdery product PQDs@SiO2. Alternatively, the reaction solution is allowed to stand for three days to form a gel-like product PQDs@SiO2.

[0084] Example 9

[0085] In this example, except that the molar ratio of APTES to lead oxide in step (1) is 30:1, the other conditions are the same as those in Example 1.

[0086] Example 10

[0087] In this example, except that the molar ratio of APTES to lead oxide in step (1) is 3:1, the other conditions are the same as those in Example 1.

[0088] Comparative Example 1

[0089] In this comparative example, except that APTES was replaced by oleylamine, other conditions were the same as those in Example 1.

[0090] Comparative Example 2

[0091] In this comparative example, APTES was replaced by oleylamine, and tetraethoxysilane was added. Other conditions were the same as those in Example 1.

[0092] Comparative Example 3

[0093] In this comparative example, 3-aminopropyltrimethoxysilane was replaced by oleylamine, and then tetramethoxysilane was added. Other conditions were the same as those in Example 2.

[0094] The QY of the powdered product PQDs@SiO2 and the gel product PQDs@SiO2 prepared in Examples 1-10 were tested, and the results are shown in Table 1.

[0095] Table 1

[0096] <![CDATA[QY of PQDs@SiO2 powder]]> <![CDATA[QY of PQDs@SiO2 gel]]> Example 1 67% 60% Example 2 65% 62% Example 3 65% 63% Example 4 63% 60% Example 5 70% 66% Example 6 63% 60% Example 7 66% 63% Example 8 64% 59% Example 9 50% 52% Example 10 45% 46%

[0097] according to Figure 2a -c It can be seen that when the PQDs@SiO2 composite is in solution, the QY of the perovskite quantum dots is 83%, which is higher than that of comparative example 1 synthesized with the traditional Lewis acid-base oleylamine and oleic acid as ligands. This indicates that the perovskite quantum dots prepared with the traditional oleylamine as ligands have no core-shell protection on the outside, and the injection of HBr aqueous solution destroys the lattice of the perovskite quantum dots to a certain extent, resulting in a lower QY. The Lewis acid-base oxysilane as a ligand can form a stable chemical bond with the quantum dots when forming a composite, and form a core-shell encapsulation structure on the surface of the quantum dots, which has a certain resistance to water and thus has a higher QY. Through different treatment methods, the composite material can obtain two forms of gel and powder. With the decrease of QY, its emission peak position also red-shifts. This is because the emission of the quantum dots decreases due to self-absorption when forming powder or gel.

[0098] like Figure 3a As shown, when hydrobromic acid is injected, the reaction is violent. After the reaction is completed, the solution is well dispersed and no precipitation is produced, which indicates that Lewis acid / alkali oxysilane acts as a ligand in the early stage of the synthesis process, making the generated quantum dots have good dispersion. Different treatment methods for the product in the later stage give gel or powder form.

[0099] The aqueous solution stability of the products of Example 1 and Comparative Examples 1-3 was tested, and the results are shown in Table 2.

[0100] Table 2

[0101] sample Initial QY 1 day 3 days 7 days 15 days Comparative Example 1 77.05% 16% 10% 6.3% 1.03% Comparative Example 2 50% 32% 20% 15% 8% Comparative Example 3 49% 35% 23% 17% 9% <![CDATA[PQDs@SiO2 powder]]> 60% 60% 60% 60% 59% <![CDATA[PQDs@SiO2 gel]]> 67% 66% 65% 65% 64%

[0102] As shown in Table 2, the QY of Comparative Example 1 drops sharply in the presence of aqueous solution. Although Comparative Examples 2 and 3 form a core-shell structure on the surface of quantum dots by adding tetraethoxysilane or tetramethoxysilane, there is no strong chemical bonding between them and the quantum dots, and they are unstable. Therefore, in the presence of water, their QY will drop significantly. However, the QY of the PQDs@SiO2 product of Example 1 does not change much after fifteen days. This is because the amino group of APTES can be anchored on the surface of quantum dots as a ligand, and can be better coated on the surface of quantum dots in the subsequent coating process, thereby reducing the invasion of water and oxygen on quantum dots. The trimethoxysilane and triethoxysilane used in Comparative Examples 2 and 3 do not have a group that can be used as a ligand, and they cannot bind to quantum dots through ligands, so the coating effect is not as good as that of Example 1. Therefore, the stability of Example 1 has been objectively improved.

[0103] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0104] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0105] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0106] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a perovskite quantum dot SiO2 composite material, characterized in that: The preparation method comprises: (1) mixing a lead source, a cesium source, a ligand, and a Lewis acid / Lewis base oxysilane with a solvent, and performing a first heating and vacuuming to obtain a first reaction system; (2) replacing the first reaction system in step (1) with a nitrogen environment, and performing a second heating to obtain a second reaction system; (3) injecting the hydrohalic acid solution into the second reaction system of step (2) to react, and cooling and separating the reaction mixture after the reaction to obtain a perovskite quantum dot SiO2 composite material; The molar ratio of the Lewis acid / Lewis base oxysilane to the lead source in step (1) is 25:1 to 5:1; The lead source in step (1) is limited to lead oxide and / or lead acetate, and the cesium source is limited to any one of cesium carbonate, cesium acetate or cesium bicarbonate or a combination of at least two thereof; The ligands include Lewis acid ligands and / or Lewis base ligands; The structure of the Lewis acid / Lewis base oxysilane in step (1) is shown in Formula 1: The wavy line segment is a straight-chain or branched alkyl group, and R includes any one of an amino group, a thiol group, a carboxyl group, a sulfonic acid group or a TOPO group, or a combination of at least two of them.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the cesium source to the lead source in step (1) is 10:1 to 1:

10.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the ligand to the lead source in step (1) is 5:1 to 2:

1.

4. The preparation method according to claim 1, characterized in that: The molar ratio of the lead source to the solvent in step (1) is 1:200 to 1:

50.

5. The preparation method according to claim 1, characterized in that: The Lewis acid ligand in step (1) includes any one of oleic acid, dodecylbenzenesulfonic acid or trioctylphosphine or a combination of at least two thereof.

6. The preparation method according to claim 1, characterized in that: The Lewis base ligand in step (1) includes any one of oleylamine, n-octylamine or thiol, or a combination of at least two of them.

7. The preparation method according to claim 1, characterized in that: The Lewis acid / Lewis base silane in step (1) includes any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane or 3-mercaptopropyltriethoxysilane, or a combination of at least two of them.

8. The preparation method according to claim 1, characterized in that: The solvent in step (1) includes any one of liquid paraffin, trioctyl phosphine or octadecene, or a combination of at least two thereof.

9. The preparation method according to claim 1, characterized in that: The terminal temperature of the first heating in step (1) is 80-110°C.

10. The preparation method according to claim 1, characterized in that: The vacuuming time in step (1) is 20 to 40 minutes.

11. The preparation method according to claim 1, characterized in that: The terminal temperature of the second heating in step (2) is 150-180°C.

12. The preparation method according to claim 1, characterized in that: The hydrohalic acid solution in step (3) is a mixed solution obtained by diluting a hydrohalic acid aqueous solution with an organic solvent.

13. The preparation method according to claim 12, characterized in that: The organic solvent includes octadecene.

14. The preparation method according to claim 1, characterized in that: The hydrohalic acid in step (3) includes any one of hydrobromic acid, hydrochloric acid or hydroiodic acid, or a combination of at least two of them.

15. The preparation method according to claim 1, characterized in that: The molar ratio of the hydrohalic acid to the lead source is 10:1 to 3:

1.

16. The preparation method according to claim 1, characterized in that: The reaction time of step (3) is 2 to 5 minutes.

17. The preparation method according to claim 1, characterized in that: The cooling in step (3) includes cooling naturally or cooling in a water bath to room temperature.

Citation Information

Patent Citations

  • Silicon dioxide coated caesium-lead-bromine-perovskite nanocrystal compound and microwave assisted heating synthesis method thereof

    CN108531173A

  • Synthesizing method of iodine-lead perovskite quantum dot

    CN109456763A